E-Commerce Web Design Analysis For Computer Sales - Agustina Srirahayu; Difa Alma Fionita (Proceeding of International Conference on Science, Health, And Technology, 2021)
CV. Anyar Komputer is a company for repair services, sales and purchases of laptops and PC computers. Customer from CV. Anyar ordinary computer from individuals and offices / companies. Current business processes at CV Anyar Komputer in recording computer or other hardware repair activities are still recorded in the ledger and there is no written evidence for customers who repair their devices, so customers have to come again to the store to ask about the status of the development of the repaired devices . From the data obtained, there were more than 10 customers who came to repair the device at CV. Anyar Computer. Meanwhile, in the process of purchasing computers, it is still recorded in the ledger, the difficulty is when doing financial reports takes a long time because the process is done manually and does not use the help of machines in making financial reports. With technological developments that force people to work quickly, CV. Anyar Komputer must develop in the transaction process and documentation in its business processes. Analysis of e-commerce needs for web student computer sales was chosen because there are already many companies and computer shops that sell website-based goods. This website-based e-commerce is designed with 4 user access rights, namely administrators, technicians, leaders, and customers. The system development method used is a prototype where the stages used are only up to the design stage. This study does not discuss the return of goods to suppliers and consumers. Business process analysis using PIECES and Data Flow Diagrams. used for data flow modeling. The results of this study are 1 databases with 6 tables designed, interface design for 4 user access rights